Prevalência da síndrome de Burnout em enfermeiros da rede hospitalar de urgência e emergência no Estado da Paraíba - BR - Dantas, Tatiana Rodrigues da Silva (2011)
Burnout syndrome is a psycho-social phenomenon which results from the association among labored demands and exigencies and personal characteristics of the individual. This syndrome occurs mainly in professionals that work in direct contact with people. Also, it is a tridimensional syndrome that is characterized by emotional exhaustion, depersonalization and a reduced sensation of professional realization. The present research aims to investigate the occurrence of Burnout Syndrome among nurses of Urgency and Emergency Hospitals in Paraíba State. Moreover, it is a descriptive research with quantitative approach, developed in six specialized hospitals in urgency and emergency in Paraíba. The sample was constituted by 110 nurses who have worked in the urgency and emergency sector. The tools used were Maslach Burnout Inventory (MBI), Human Service Survey (HSS) version, and the Inventory of Work and Illness Risk (in Portuguese, ITRA). The data were tabled and analyzed using the SPSS software, 15.0 version. Furthermore, the research adopted significance level of 5%, and values to p < 0.05 were considered significant. The chi-square test was used to verify the association between variables. Also, all ethical aspects of researches with humans were considered in this research. The results showed predominance of female nurses, young, single and childless. Furthermore, 54.5% live in situation of multiple jobs, 49.1% works from 20 to 44 hours a week, and 30.9% of them declared that have some kind of extra-activity different from nursing assistance. In relation to the work time in nursing, actuation in hospital and in urgency and emergency services, the research observed predominance of professionals with less than five years of actuation. 61.8% are service renders or encoded ones. 31% of the nurses presented a high level of EE, 49.1% presented it in medium one. In addition, 28.2% presented DP in high level, 54.5% presented it in medium one, and 23.6% presented reduced personal accomplishment. 82.7% of the nurses presented BS, 59.1% of them in a moderated level and 23.6% in serious one. It was noted that there is an association statistically significant between the occurrence of BS and exposition to the following variables: non-repetitive tasks (p-value = 0.012), tasks has not been well defined (p-value = 0.004), precarious service conditions (p-value = 0.014), burnout (p-value = 0.000), emotional exhaustion (p-value = 0.033), stress (p-value = 0.001), overload (p-value = 0.001), frustration (p-value = 0.002), insecurity (p-value = 0.015), and lack of recognition of my performance (p-value = 0.041). Also, recognition is considered as a protection factor against BS development (RR = 0.82/CI = 0.71; 0.94). The research concludes that nurses which work in urgency and emergency services presents an expressive level of illness because of the lasting contact with the work conditions of this kind of service. It is necessary to implement strategies that focus on the elimination, reduction or, minimally, the control of variables associated to Burnout Syndrome development among nurses of urgency and emergency services. Then, these strategies aim to the health reestablishment of these professionals, and the sanity preservation of nurses that are still healthy. Therefore, professionals, users and managers will obtain benefits.